Histological Evaluation of Some Skin Lesions of Tick Bites in Sheep - Mustafa, Bahzad (University of Thi-Qar Journal of agricultural research, 2025)
In naturally infested sheep, two genera and four species of Ixodidae, two genera and two species of mites, two genera and two species of lice, three genera and three species of myiasis, and three genera and three species of fleas. Highly infested, as described in sheep, with Arachnida at 55%, comprising 46% Hard ticks and 9% Mites. The overall number of skins refused to the tanning industry was 100 (21.21%) in sheep. Histological and blood values analysis of the skin of sheep repeatedly infested with the Hyalomma anatolicum anatolicum was studied in vitro. Infiltration of neutrophils, macrophages, and lymphocytes adjacent to the tick bite site was observed. In this review, the presence of ectoparasites affected both the red and white blood cell series of hematological parameters. Among the main parameters analyzed, hematocrit, red blood cells, hemoglobin, and lymphocytes showed reductions, while eosinophils, neutrophils, and basophils increased in infested animals as a result of the host immune response. A t-test, p < 0.05, in this study reveals a statistically significant difference in blood values between individuals with naturally infested ectoparasites. This study highlights the species of Ixodidae and other ectoparasites (mites, myiasis, fleas, and lice) that cause various patterns of cutaneous lesions (as observed through histopathology) in sheep, which affects their industry.